Pengaruh Latihan Four Quadrant Jump Terhadap Peningkatan Tinggi Ollie Pada Skateboarder - Waskito, Gigih Ngesti, Arif Pristianto, SSt.FT.,M.Fis (2017)
Background: Skateboard in Indonesia providing an opportunity for someone to reach achievement. But there's lack of knowledge about improving basic skills in skateboarding that can effect on performance decreasing. Ollie is one of the basic skateboard techniques that requiring leg muscle power. One exercise program to improve power is plyometric exercises, such as Four Quadrant Jump. So that makes researchers interested in conducting research on the effects of Four Quadrant Jump to increase a high Ollie on skateboarder. Objective: The aim of this study was to determine the effect of exercise Four Quadrant Jump to a high increase Ollie on skateboarder. Methods: The study was quasy experimental design and methods of pre-test and post-test with control group design. Respondents consisted of 20 people, divided into two groups: 10 people treated group (granting exercise Four Quadrant Jump) and 10 control group (no exercise). Research carried out for 4 weeks with exercise 3 times per week. Ollie height measurements carried out per week using the horizontal bar as barriers leap. Data were analyzed using the Wilcoxon test and Mann-Whitney test. Result: The influence of pre and post test dependent height Ollie p-value of 0.004 was obtained that there are the effects of exercise Four Quadrant Jump to the height Ollie. While the influence of different test independent pre and post test p-value higher Ollie gained 0.00, so it is concluded that there are differences in height Ollie improvement in the treatment group and the control group. Conclusion: High Ollie had shown an increase with plyometric exercises in the form of exercise Four Quadrant Jump.